Tectonic evolution of the Loncopué trough: Structure of the Quaternary Huecú depocenter and its relation to the sedimentation and volcanism - Vera, E.A.R. (2009)
The Huecú basin is located at the central part of the large Loncopué retroarc trough. Its volcanic, volcaniclastic, lacustrine and fluvial filling is directly related to neotectonic activity in the area. The basaltic eruptions are reflecting different pulses associated with the development of extensional faults and tensional fractures. Geophysical potential methods have identified basement involvement in the extensional deformation that affected the Tertiary sequences of the area during the last 5 Mys. Neotectonic features in Quaternary volcanic sequences suggest the persistence of these subsidence mechanisms in the Huecú depocenter. These faults are directly connected to the basement segmentation identified by gravimetric and mag-netometric studies. The historical floods produced by the Agrio river damming, are related to fisural eruptions and demons-trate the high probability that retroarc volcanic eruptions may occur again. The recognition of flooded areas that are forming the youngest sedimentary levels in the Huecú depocenter shows potential areas of active retroarc spreading in the Neuquén area associated with neotectonic and seismic processes.